Analysis of Fe3O4 thin film optical properties prepared from the iron sand of Tiram Beach, Padang Pariaman Regency, West Sumatra using sol-gel spin coating method. - Nidya Yulfriska; Ramli Ramli; Yenni Darvina (PILLAR OF PHYSICS, 2017)
Research on magnetic oxide is growing very rapidly. This magnetic oxide can be found in nature that is iron sand. Iron sand is a deposition of sand containing iron ore that many exist along the beach. One of the beaches in West Sumatra containing iron sand is Tiram Beach, Padang Pariaman District, Sumatera Barat. The content of iron sand is generally in the form of magnetic minerals such as magnetite, hematite, and maghemit. Magnetite contained in iron sand has excellent properties that can be developed into thin films that can later be applied to magnetic sensors. The purpose of this research is to investigate the optical properties of the Fe3O4 thin films, prepared from iron sand of Tiram Beach, Padang Pariaman District, Sumatera Barat by Sol-Gel Spin Coating Method. This type of research is an experimental research. The iron sand obtained from nature is first purified using permanent magnets, then made in nanoparticle size using the HEM-E3D tool. Then, the process of making thin film with sol-gel spin coating method. In this research variation of rotation speed of spin coating is 1000 rpm, 2000 rpm, 2500 rpm and 3000 rpm. The characterization tool in the research of optical properties analysis used is UV-VIS Spectrophotometer. The value of transmittance is 32,1%, 32,2% and 32,7% respectively. The absorbance value is 96,721% - 31,247%, 95,428% - 33,785% and 93,54% - 33,551% respectively. While the reflectance values are 33,2%, 33,7% and 34,2%, respectively. So it can be concluded that the greater the speed of rotation the thickness of the thin layer will be smaller, resulting in the transmittance and reflectance will be greater, while the absorbance will be smaller. Energy gap obtained from this research is 3,75 eV, 3,75 eV and 3,74 eV. So the average energy gap obtained is 3,75 eV